Voiding dysfunction - A review - Sripathi V (Wolters Kluwer Medknow Publications, 2005)
In a child who is toilet trained the sudden onset of daytime wetting with frequency or urgency is alarming to the parents. Initially this subject was subdivided into a number of descriptive clinical conditions which led to a lot of confusion in recognition and management. Subsequently, the term elimination dysfunction was coined by Stephen Koff to emphasise the association between recurrent urinary infection, wetting, constipation and bladder overactivity. From a urodynamic point of view, in voiding dysfunction, there is either detrusor overactivity during bladder filling or dyssynergic action between the detrusor and the external sphincter during voiding. Identifying a given condition as a ′filling phase dysfunction′ or ′voiding phase dysfunction′ helps to provide appropriate therapy. Objective clinical criteria should be used to define voiding dysfunction. These include bladder wall thickening, large capacity bladder and infrequent voiding, bladder trabeculation and spinning top deformity of the urethra and a clinically demonstrated Vincent′s curtsy. The recognition and treatment of constipation is central to the adequate treatment of voiding dysfunction. Transcutaneous electric nerve stimuation for the treatment of detrusor overactivity, biofeedback with uroflow EMG to correct dyssynergic voiding, and behavioral therapy all serve to correct voiding dysfunction in its early stages. In established neurogenic bladder disease the use of Botulinum Toxin A injections into the detrusor or the external sphincter may help in restoring continence especially in those refractory to drug therapy. However in those children in whom the upper tracts are threatened, augmentation of the bladder may still be needed.